Risk Factors andthe Most Common Initial Symptoms of Acute Lymphoblastic Leukemia in Children - Hashemizadeh H; Jafarzadeh A; Broumand H (Iran University of Medical Sciences, 2011)
Background: The factors involve in Leukemia are not fully understood. However, research has shown the relationship between this disorder and some risk factors. The aim of this study was to determine risk factors involved in acute lymphoblastic leukemia and its most prevalent clinical manifestations in children residing in Khorasan province.   Materials and Methods: It was a case - control study. The adequate sample size was 100 cases and 400 controls. Controls were matched with cases regarding their sex, age and habitation. Data was collected by face to face interview with patients' mothers and the questionnaires were completed by the investigator. Data was analyzed by conditional logistic regression using SPSS-PC (v.14).   Results: According to the findings of this study, maternal use of oral contraceptives, living in proximity to high voltage power lines, in-utero ionizing radiation exposure, pesticide exposure in fathers and paternal occupation and parental smoking had a significant relation with this type of cancer (p<0.05).the most prevalent mitial clinical manifestations were lethargy and weakness, fever, leg pain, cervical lymphadenopathy, bleeding, abdominal pain and cold symptoms respectively   Conclusion: According to the results of this study, it seems that environmental factors play an important role in etiology of this kind of cancer. Knowledge abort this fact helps us to find appropriate ways to prevent this disease in children.